KEPEMIMPINAN TRANSFORMASIONAL SEBAGAI KATALISATOR INOVASI: MENDORONG ADOPSI CLOUD COMPUTING UNTUK KEUNGGULAN BERSAING - Yubarda, Erliza; Giatman, M.; Maksum, Hasan; Lapisa, Remon; Fadhilah, Fadhilah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study analyzes the function of transformational leadership as a driver of innovation in promoting the adoption of cloud computing to achieve sustainable competitive advantage. Using a systematic literature review (SLR) approach, this study combines the results of six leading articles published between 2018 and 2025. The analysis results show that transformational leadership, using intellectual stimulation, inspirational motivation, and cultural change, can generate innovation in organizations that directly supports cloud adoption. Cloud computing further enhances organizational responsiveness and innovation capacity, enabling companies to respond more quickly to market changes. The research findings confirm that competitive advantage stems not only from technological aspects but also from the dynamic capabilities shaped by transformational leaders who align cloud resources with strategic objectives. This study contributes to filling a gap in theory by proposing a sequential mediation mechanism linking transformational leadership, organizational innovation, cloud adoption, and competitive advantage. Implications for management recommend that organizations focus on digital-based leadership training and ensure that cloud resource allocation is aligned with corporate strategy. Keyword: Transformational Leadership; Innovation; Cloud Computing; Organizational Agility; Competitive Advantage Abstrak: Penelitian ini menganalisis fungsi kepemimpinan transformasional sebagai penggerak inovasi dalam mendorong penerapan cloud computing untuk meraih keunggulan kompetitif yang berkelanjutan. Melalui pendekatan tinjauan pustaka sistematis (SLR), studi ini menggabungkan hasil dari enam artikel terkemuka yang diterbitkan antara tahun 2018 hingga 2025. Hasil analisis menunjukkan bahwa kepemimpinan transformasional, dengan menggunakan stimulasi intelektual, motivasi inspirasional, serta perubahan budaya, dapat menghasilkan inovasi dalam organisasi yang mendukung langsung penerapan cloud. Cloud computing selanjutnya meningkatkan responsivitas organisasi dan kapasitas inovasinya, sehingga perusahaan lebih cepat dalam merespons perubahan pasar. Temuan penelitian menegaskan bahwa keunggulan kompetitif tidak hanya berasal dari aspek teknologi, tetapi juga dari kemampuan dinamis yang dibentuk oleh pemimpin transformasional yang menyelaraskan sumber daya cloud dengan tujuan strategis. Studi ini memberikan kontribusi dalam mengisi kekurangan teori dengan mengusulkan mekanisme mediasi berurutan yang menghubungkan antara kepemimpinan transformasional, inovasi organisasi, penerapan cloud, dan keunggulan kompetitif. Implikasi bagi manajemen merekomendasikan agar organisasi fokus pada pelatihan kepemimpinan yang berbasis digital dan memastikan alokasi sumber daya cloud selaras dengan strategi perusahaan. Kata kunci: Kepemimpinan Transformasional; Inovasi; Cloud Computing; Kelincahan Organisasi; Keunggulan Bersaing